1. Разложите на множители : 9-(2с-1)^2

2. Преобразуйте в многочлен выражение: -b(b+5)-(b-6)(b+6)

ПОМОГИТЕ ПОЖАЛУЙСТА СРОЧНО!!!

1

Ответы и объяснения

Лучший Ответ!
  • Участник Знаний
2013-07-29T21:49:04+04:00
1) 9 - (2C - 1)^2 = 9 - (4C^2 - 4C + 1) = 9 - 4C^2 + 4C - 1 = 
= - 4C^2 + 4C + 8 = 4*(-C^2 + C + 2)
.......................................
-C^2 + C + 2 = 0
D = 1 -4*(-1)*2 = 9
V D = 3
C1 = (-1 + 3 ) \ -2 = - 1
C2 = -4\-2 = + 2
ОТВЕТ: 4*(С + 1)*(С - 2)
..........................................
2) -B*(B+5)-(B-6)*(B+6) = -B^2 - 5B - (B^2 - 36) = -B^2 - 5B - B^2 + 36
= - 2B^2 - 5B + 36